THE RELATIONSHIP BETWEEN HAPPINESS AND BRAINROT IN EARLY ADULTHOOD - Dian Kristina Tambunan,; Malida Fatimah,; Katrim Alifa Putrikita, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The intensive use of social media among individuals in early adulthood has the potential to cause negative psychological effects, one of which is brainrot. Brainrot refers to a condition characterized by cognitive fatigue, concentration difficulties, and passive overexposure to digital content. Happiness is suspected to play an important role in reducing such tendencies. This study aims to examine the relationship between happiness and the level of brainrot among early adults. The research employed a quantitative approach with a correlational design. A total of 196 participants aged 20 to 30 years who actively use social media were involved. Data were collected using a happiness scale and a brainrot scale developed by the researcher. The data were analyzed using Pearson’s correlation test. The results showed a significant negative correlation between happiness and brainrot (r = -0.176; p = 0.014), indicating that individuals with higher levels of happiness tend to experience lower levels of brainrot